2021
DOI: 10.3389/fcell.2021.687942
|View full text |Cite
|
Sign up to set email alerts
|

CXCL2 Impairs Functions of Bone Marrow Mesenchymal Stem Cells and Can Serve as a Serum Marker in High-Fat Diet-Fed Rats

Abstract: In modern society excessive consumption of a high-fat diet (HFD) is a significant risk factor for many diseases such as diabetes, osteoarthritis and certain cancers. Resolving cellular and molecular mechanisms underlying HFD-associated disorders is of great importance to human health. Mesenchymal stem cells (MSCs) are key players in tissue homeostasis and adversely affected by prolonged HFD feeding. Low-grade systemic inflammation induced by HFD is characterized by increased levels of pro-inflammatory cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
0
13
2
Order By: Relevance
“…In the short-term exposure to the HFD-SFAs (4 weeks), we observed the induction of apoptosis in bone marrow neutrophils, which could be probably due to an excessive engulfment of TGs ( Ortega-Gomez et al, 2017 ) and not to the trafficking of senescent neutrophils back to the bone marrow, as CXCR4 expression in circulating and bone marrow neutrophils and CXCL12 expression in bone marrow cells at fasting were unaffected ( De Filippo & Rankin, 2018 ). In addition, we found that the HFD-SFAs induced a remarkable elevation of fasting serum CXCL2, which is a chemokine associated with the onset of inflammation and recently identified to cause early senescence and a functional decline of stem cells from bone marrow mesenchymal niche during the development of obesity in rats ( Bi et al, 2021 ). These findings are in line with previous in vitro reports showing that palmitic acid was involved in mediating apoptosis and pro-inflammatory response in immune cells, which were effects not observed with oleic acid, EPA or DHA ( Hidalgo et al, 2021 , Radzikowska et al, 2019 ).…”
Section: Discussionmentioning
confidence: 82%
“…In the short-term exposure to the HFD-SFAs (4 weeks), we observed the induction of apoptosis in bone marrow neutrophils, which could be probably due to an excessive engulfment of TGs ( Ortega-Gomez et al, 2017 ) and not to the trafficking of senescent neutrophils back to the bone marrow, as CXCR4 expression in circulating and bone marrow neutrophils and CXCL12 expression in bone marrow cells at fasting were unaffected ( De Filippo & Rankin, 2018 ). In addition, we found that the HFD-SFAs induced a remarkable elevation of fasting serum CXCL2, which is a chemokine associated with the onset of inflammation and recently identified to cause early senescence and a functional decline of stem cells from bone marrow mesenchymal niche during the development of obesity in rats ( Bi et al, 2021 ). These findings are in line with previous in vitro reports showing that palmitic acid was involved in mediating apoptosis and pro-inflammatory response in immune cells, which were effects not observed with oleic acid, EPA or DHA ( Hidalgo et al, 2021 , Radzikowska et al, 2019 ).…”
Section: Discussionmentioning
confidence: 82%
“…The expression of CXCL2 was negatively correlated with BMD ( 17 ). Neutralization of CXCL2 prevented bone destruction in lipopolysaccharide-challenged mice ( 36 ), while supplement of CXCL2 in culture medium led to cellular senescence and impaired differentiation of MSCs ( 37 ). In our study, differential gene analysis showed that the expression of Cxcl2 was significantly up-regulated at 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…They induce chemotaxis in cells like neutrophils, lymphocytes, and monocytes, and are intimately linked to vasculitis progression, mediating early OA synovitis [22]. CXCL2 belongs to the chemokine superfamily, with its encoded secreted protein playing a role in immune modulation and in ammation [23]. CXCL8 promotes chondrocyte apoptosis and inhibits their proliferation by in uencing the JAK-STAT, NF-kB, and JNK MAPK signaling pathways and enhancing the expression of other pro-in ammatory cytokines [24].…”
Section: Discussionmentioning
confidence: 99%